Heterometallic complexes with cube-type [MTi3N4] cores containing Group 10 metals in a variety of oxidation states. Issue 21 (30th April 2015) - Martínez-Espada, Noelia; Mena, Miguel; Pérez-Redondo, Adrián; Varela-Izquierdo, Víctor; Yélamos, Carlos
Abstract : The metalloligand [{Ti(η 5 -C5 Me5 )(μ-NH)}3 (μ3 -N)] is capable of stabilizing Group 10 metals in the oxidation states 0, ii oriv . Abstract : Treatment of [{Ti(η 5 -C5 Me5 )(μ-NH)}3 (μ3 -N)] (1 ) with one equivalent of [Ni(cod)2 ] (cod = 1, 5-cyclooctadiene) in toluene at 60–80 °C and subsequent addition of diphenylacetylene, trans -stilbene or triphenylphosphane afforded the nickel(0) complexes [LNi{(μ3 -NH)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (L = PhCCPh (2 ), PhCHCHPh (3 ), PPh3 (4 )). The nickel(ii ) complex [I2 Ni{(μ3 -NH)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (5 ) was prepared by analogous addition of iodine to the solution obtained from the heating of1 and [Ni(cod)2 ]. Treatment of1 with one equivalent of [Pd(dba)2 ] (dba = dibenzylideneacetone) in toluene at room temperature led to the palladium(0) complex [(dba)Pd{(μ3 -NH)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (6 ). Compound6 reacted immediately with chloroform-d1 to give the palladium dichloride derivative [Cl2 Pd{(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ-NH)(μ3 -N)}] (7 ), which was prepared by treatment of1 with [PdCl2 (cod)] at room temperature. Addition of iodine to a toluene solution of6 afforded the analogous palladium(ii ) derivative [I2 Pd{(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ-NH)(μ3 -N)}] (8 ). Complex6 reacted with two equivalents of dimethylacetylenedicarboxylate (dmad) to give the metallacyclopentadiene palladium(ii ) complex [{(MeOOC)4 C4 }Pd{(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ-NH)(μ3 -N)}] (9 ) via oxidative coupling. The treatment of1 with [Pt(nbe)3 ] (nbe = norbornene) in toluene at room temperature gave the platinum(0) complex [(nbe)Pt{(μ3 -NH)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}] (10 ). Compound10 reacted with excess iodine to afford the platinum(iv ) ionic derivative [I3 Pt{(μ3 -NH)3 Ti3 (η 5 -C5 Me5 )3 (μ3 -N)}]2 (I3 )(I5 ) (11 ) via an intermediate platinum(ii ) complex [I2 Pt{(μ3 -NH)2 Ti3 (η 5 -C5 Me5 )3 (μ-NH)(μ3 -N)}] (12 ). The X-ray crystal structures of5, 8, 9 and11 have been determined.